Consideraciones de política criminal sobre el delito de negociaciones incompatibles con la función pública: una reconstrucción de su ilicitud como puesta en peligro contra la voluntad estatal - Rusca, Bruno (2023)
Based on the distinction drawn by R. A. Duff between attacks and endangerments as two different kind of wrongs, this paper advocates a view of the crime of conflict of interest in the public sector as implicit endangerment against government decisions. This view is supported by different empirical studies, which demonstrate that, in scenarios of conflict of interest, although agents do not act with a deliberate purpose of benefiting themselves, their decisions tend to privilege their private interests. In addition, it is argued that, according to the perspective defended, the scope of the offense should include interests and acts of a non-economic nature. It should be clarified that the purpose of this paper is to contribute to the development of a normative theory of negotiations incompatible with public office which determines how this crime should be regulated, regardless of the specific way in which each legislation defines such behavior.